DESAIN PENGISIAN AIR OTOMATIS PADA KOLAM IKAN NILA BERBASIS ARDUINO UNO - Raihan Nuraditya Pratama; Ryuken, Mochammad Rifan Arkaan, Putra Bagus, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study aims to design and implement an automatic water refilling system for tilapia fish ponds using the Arduino Uno microcontroller. The system utilizes an ultrasonic sensor to detect water levels in real- time and controls a water pump through a relay module. The primary objective is to maintain the water volume stability in the pond to support the health and growth of tilapia fish. Testing results indicate that the system successfully detects changes in water volume, activating the water pump when the distance between the sensor and the water surface exceeds 5 cm and automatically turning it off when the distance is less than 5 cm. By implementing this automated system, challenges such as water level fluctuations and declining water quality can be minimized, contributing to the success of integrated aquaponics-based tilapia fish farming. This research is expected to provide an innovative solution for enhancing the efficiency of tilapia pond management and meeting the demands of sustainable aquaponics systems